Church members at a Christmas party - Ted Sahl (photographer):::Creator::::::::::::
Photograph shows five men posing at a United Fellowship Metropolitan Community Church social event, possibly a Christmas party. The man at the far left is Jim Junkin, a founding member of the Metropolitan Community Church, San Jose.